Elephant grass under grazing. I. Factors affecting dry matter intake - Hillesheim, Amaro; Corsi, Moacyr (Pesquisa Agropecuaria Brasileira, 2014)
A study was carried out to evaluate the effects of grazing pressure (GP), use of concentrates, nutritive value and climate, upon intake of Elephant Grass (Pennisetum purpureum, Schum.) cv. Napier, under grazing. The pasture was grazed during three periods: beginning, middle and end of summer, under grazing pressures of 12, 8 and 4% of live weight (LW) in relation to the accumulated dry matter (DM). A group of nine heifers was used. Levels of concentrates were: 0.00; 1.75 and 3.50 kg/animal/day. The experiment was carned out in a 20 year old pasture at ESALQ, Piracicaba, SP, which has been grazed for 15 years. Forage dry matter intake was 1.65; 1.33 and 1.17% of LW, respectively for the levels of concentrate, whereas total DM intake was 1.65; 1.92 and 2.26% of LW, which resulted in a substitution rate of 0.409. Forage intake was not affected by GP (P < 0.05) but was significantly affected by grazing periods. Pasture factors such as availability, density, leaf proportion and height did not affect intake. In vitro DM digestibility affected positively forage intake and maximum temperature negatively in one of the equations; in another equation global radiation affected positively forage intake and maximum temperature negatively.